2011
DOI: 10.1007/s10147-011-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

First case of vaginal radical trachelectomy in a pregnant Japanese woman

Abstract: A diagnosis of cervical cancer during pregnancy poses difficult management and ethical problems. Survival of the patient is the foremost concern, but fetal viability and well-being must also be addressed. Radical trachelectomy (RT) has recently begun to be performed as a possible treatment modality for early stage invasive uterine cervical cancer in pregnant patients who would like to continue their pregnancy. A 32-year-old Japanese woman visited a local hospital for prenatal care, and was diagnosed with a FIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…As is well known, RT is performed through either the abdominal or vaginal route. As shown in Table , most operations seem to have been performed through the abdominal route in Japan . Vaginal RT for pregnant patients has been performed only in our institute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, RT is performed through either the abdominal or vaginal route. As shown in Table , most operations seem to have been performed through the abdominal route in Japan . Vaginal RT for pregnant patients has been performed only in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…However, this operation for pregnant patients with the disease is still experimental. As far as we know, there have been only four reports on nine patients, including our case, published so far in Japan . We started vaginal RT for pregnant patients with this condition in 2010, and have conducted operations for five patients.…”
Section: Introductionmentioning
confidence: 94%
“…12,18 The histological types were squamous cell carcinoma (SCC) in most patients, adenocarcinoma (adenoCa) in 6 patients, 6,8,9,11,12,19 adenosquamous cell carcinoma in 1 patient, 9 and papillary mucinous adenoCa in 1 patient. 18 Table 1 gives a picture of radical trachelectomy cases during pregnancy and mentions tumor characteristics and pregnancy outcome.…”
Section: Resultsmentioning
confidence: 99%
“…14 Prelabor rupture of the membranes occurred in 3 of 18 second-trimester cases, 4,6,8 1 at 26 weeks 6 and 2 after the 34th week of gestation. 4,8 Among the 18 patients operated on in the second trimester, significant prematurity less than 34 weeks occurred in only 2 pregnancies (29 and 26 weeks of gestation). 6,9 It has been demonstrated that the uterine arteries during vaginal radical trachelectomy (VRT) or ART may be preserved, and many techniques have been developed to conserve the ascending branches of the uterine arteries.…”
Section: Resultsmentioning
confidence: 99%
“…La traquelectomía radical, que está indicada en casos de carcinoma cervical en estadios iniciales cuando la paciente desea preservar la fertilidad, se ha descrito en pacientes embarazadas durante el segundo trimestre (como toda cirugía en la gestación, tiene mejor pronóstico si se realiza en las semanas 16-18), aunque en muy pocos casos y asumiendo un riesgo muy elevado de rotura prematura de membranas, parto prematuro, sangrado materno abundante y pérdida fetal 8 .…”
Section: Discussionunclassified